1993
DOI: 10.1108/14635789310031432
|View full text |Cite
|
Sign up to set email alerts
|

Revisionary Freeholds: Problems with Over‐renting

Abstract: Examines the valuation of property investments let at rents in excess of their estimated rental values. Summarises the conventional and contemporary approaches to market valuation. Exposes the limitations of the models via an examination of some actual valuations taken from the UK property market. Concludes that future rental growth prospects must be dealt with explicitly in these valuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Against such rapid change and the consequent risk of premature obsolescence, the lessees appear completely unprotected -except in so far as the leases may enable them to change brand and image. The implications of this could be that leisure property lessees face a worse scenario than that of many office tenants during the early 1990s when 'over-renting' occurred, 81 for over-renting will occur unless leisure rents not only do not fall back but actually increase above the rate of projected inflation year on year.…”
Section: Discussionmentioning
confidence: 99%
“…Against such rapid change and the consequent risk of premature obsolescence, the lessees appear completely unprotected -except in so far as the leases may enable them to change brand and image. The implications of this could be that leisure property lessees face a worse scenario than that of many office tenants during the early 1990s when 'over-renting' occurred, 81 for over-renting will occur unless leisure rents not only do not fall back but actually increase above the rate of projected inflation year on year.…”
Section: Discussionmentioning
confidence: 99%
“…A number of commentators (for example, Martin, 1991;Crosby and Goodchild, 1992;French, 1992;Epstein, 1993) have put forward the use of growth explicit market valuation techniques to help solve these technical problems. As real value is a growth implicit model (in so far as the growth rate is only used to calculate the reversionary discount rate), and many practitioners were anxious to consider the future date at which the rental value might ® nally recover to overtake the rent ® xed under the lease, the short-cut DCF model gained most practical support (see Baum and Crosby (1995a) for a review of the debate on overrented properties in the UK).…”
Section: Market Valuation For Over-rented Investment Propertiesmentioning
confidence: 98%
“…Crosby and Goodchild (1992) and Baum and Crosby (1995b) examined the risk of the contract rent secured on high-quality tenants on long leases with upwards-only rent reviews and suggested it had the qualities of an illiquid bond. Where tenant covenant was very strong, the term discount rates were adjusted downwards within the short-cut DCF model to compensate.…”
Section: Market Valuation For Over-rented Investment Propertiesmentioning
confidence: 99%
“…The example used by Crosby and Goodchild (1992) was of a Central London office building let for 20 years on full repairing and insuring terms with five-year reviews at a passing rent of £2million p.a.…”
Section: Tax Implicationsmentioning
confidence: 99%